Implementation of MEMS Accelerometer for Velocity-based Seismic Sensor - Amalia Cemara Nur'aidha; Sukir Maryanto; Didik R. Santoso (IAES Indonesia Section, 2018)
Micro Electro Mechanical System (MEMS) accelerometer is commonly used as acceleration-based vibration sensor. The MEMS accelerometer is small device, simple in the implementation design, and relatively inexpensive. But in some fields of application, due to low frequency operation and also small magnitude of the measured signal, for example in seismology, velocity-based vibration sensor is usually more desirable than acceleration-based sensor. In this research, a velocity-based vibration sensor has been developed using MEMS Accelerometer device e.g. MMA7361L. The acceleration-based vibration signal from the MMA7361L is converted into a velocity-based vibration signal by using an integrator circuit module. This module is assembled by using a band-pass filter and an integral-amplifier. The laboratory test shows that the developed sensor system could detect both low and high-frequency vibration signals in velocity-based with good result. The sensor system has a frequency range of 0.02Hz to 148Hz. It is wider frequency than the geophone (seismic sensor), thus the velocity-based MEMS sensor system has capability for geophone replacement.